RANCANG BANGUN SISTEM SMART ECO-TOURISM BERBASIS VIRTUAL REALITY UNTUK MENDUKUNG PARIWISATA BERKELANJUTAN DI KABUPATEN AGAM, SUMATERA BARAT - Indra Yones; Titi Sriwahyuni; Yeka Hendriyani; Jusmardi Jusmardi (STKIP Pesisir Selatan, 2026)
Sustainable tourism has become an important approach in managing tourist destinations that prioritize environmental preservation and community welfare. The Maninjau Lake area in Agam Regency, West Sumatra, has significant natural tourism potential but still faces limitations in digital promotion media and tourist understanding of eco-tourism concepts. This study aims to design and develop a Smart Eco-Tourism system based on Virtual Reality as a promotional and educational media for sustainable tourism. This research uses the Prototype method which allows system development to be carried out iteratively and focuses on user needs. The system development process includes requirement analysis, prototype design, implementation, and system testing. The developed system is capable of presenting interactive 3D tourism maps and virtual exploration experiences of Maninjau Lake tourist destinations. Functional and usability testing results indicate that the system works properly and is easy to use by users. The integration of Virtual Reality technology into Smart Eco-Tourism systems provides an interactive digital tourism promotion model while supporting environmental awareness and sustainable tourism education.